Substrates and container types on rooting of peach cv. Okinawa hardwood cuttings of different diameters - Tofanelli, M. B D (2004)
Propagation by hardwood cuttings is an important technique for producing plant of many species. The technique is usually easy and inexpensive and makes it possible to high plants. But it is not commonly used for peach propagation in Brazil. The objective of this study was to evaluate the effects of different substrates, container types and cutting diameters on rooting of peach hardwood cuttings. The cuttings (two size groups, diameters of 2-6 mm and 6-10 mm) were inserted in six substrates (carbonized rice husk, vermiculite, washed sand, carbonized rice husk + vermiculite, carbonized rice husk + washed sand and vermiculite + washed sand, each 1:1 v/v), each in three types of containers (plastic bag, plastic tray and polystyrene tray). The best rooting occurred with smaller cuttings (47%) and larger cuttings (38%) in plastic bag with vermiculite, and with smaller cuttings in plastic bag with washed sand + vermiculite (33%). While these rooting percentages were unsatisfactory for commercial propagation, the results are encouraging and suggest need for more investigation to improve rooting.